The visibility of dissident masculinities in digital media: Interdisciplinary theoretical analysis with a gender perspective - Carranza-Benites, Renzo (2025)
Background: Over the years, digital media have become the primary platformsfor the circulation and production of identity narratives, specifically around the creationof new masculinities. In this vein, dissident masculinities have emerged as anantagonistic proposal to hegemonic masculinity and with growing visibility under acanopy of ambivalence. On the one hand, digital media offer self-definition, resistance,and the creation of a sense of community; on the other, they generate a stereotypical,binary, and hierarchical vision that censors diversity. Objective: The article aims to(1) analyze how digital representations of masculinity are configured and theirpsychosocial implications through a critical review from the perspective ofcommunication, social psychology, and gender, as well as (2) propose a new theoreticalmodel. Results: The main finding is that most existing evidence focuses on non-Latincontexts, with a primary emphasis on visibility rather than narrative quality, therebyexcluding the exploration of subjective effects on subjects with diverse identities.Conclusion: Based on this, a conceptual model is outlined that seeks to link medianarratives, psychosocial processes, and social imaginaries.